Fenestrated screws in osteoporotic spine—Is there an association between the cement distribution and DEXA scan T score? - Saumyajit Basu; Rohan B Gala; Amitava Biswas; Anil M Solanki (Indian Spine Journal, 2023)
Purpose: Cement distribution in spinal stabilization with fenestrated screws is unpredictable in patients with osteoporosis. The objective of our study was an assessment of cement distribution while using fenestrated screws and to establish an association between cement distribution and the Dual Emission X-ray Absorptiometry (DEXA) scan T scores. Materials and Methods: Osteoporotic patients who underwent spinal stabilization with fenestrated screws by a single surgeon with a minimum follow-up of one year were included. Cement distribution (four zones comprising the vertebral body and the pedicle), a pattern of distribution (concentrated or scattered) and cement leakage were assessed on CT scans. Patients were categorized into two groups based on their DEXA scan T scores to test an association between the pattern of distribution of cement and the scores. Clinical improvement was determined using visual analogue scale and Oswestry disability index scores. Results: A total of 126 screws were analyzed in 20 patients with a mean age of 69 years and a mean follow-up of 18 months. Out of 126 screws, 114 (90.47%) had cement in Zones 1 and 2. In total, 58 screws had a concentrated pattern of distribution of cement, whereas 68 screws had a scattered distribution, and the odds ratio of a scattered pattern of distribution was 6.31:1 if the DEXA scan T score was “below (−)3.0.” Clinical improvement was calculated in percentage of change from the preoperative value (mean % visual analogue scale change = 65.13 ± 7.59 and mean % Oswestry disability index change = 43.14 ± 7.24). Conclusion: The pattern of cement distribution in fenestrated screws relates well with the DEXA scan T scores and their usage should be strongly considered in patients with poorer scores. However, there is no relevant difference between the pattern of distribution and the clinical outcome.